Relevansi Gaya Kepemimpinan Kepala Program Studi (Prodi) dalam Menentukan Strategi Peningkatan Kualitas Program Studi untuk Mencapai Indikator Kinerjautama (IKU) - Dita Fatmawati; Lailatul Fitriyah (LP. Ma'arif Janggan Magetan, 2023)
This research uses a qualitative approach, namely field research (Field Reseach). In this study the method used to collect data by (1) Observation, (2) Interview, (3) Documentation.the location of this research was conducted at Nurul Jadid Paiton University Probolinggo, and the population is the head of study, lecturers and students. From the results of the analysis conducted by the researcher that, there are three targets for the development of Key Performance Indicators: first, improving the quality of learning and higher education relations, second improving the quality of lecturers and education staff and finally the realization of quality governance of the Directorate General of Higher Education.Key performance indicators have detailed performance targets called SKP (employee performance targets) which have target values that must be achieved each year. In improving the quality of good Key Performance Indicators, a leadership style is needed that can innovate and can coordinate all subordinates properly and correctly. Therefore, the style carried out by several heads of study programs in determining strategies to improve the quality of study programs is to apply democratic and transformational leadership styles.